The “chameleon” sellar lesions: a case report of unexpected sellar lesions - Bove, Ilaria; Franca, Raduan Ahmed; Ugga, Lorenzo; Solari, Domenico; Elefante, Andrea; De Caro, Maria Laura Del Basso; Cavallo, Luigi Maria (Frontiers in Neurology, 2023)
Introduction The sellar region and its boundaries represent a challenging area, harboring a variety of tissues of different linings. Therefore, a variety of diseases can arise or involve in this area (i.e., neoplastic or not). A total of three challenging cases of “chameleon” sellar lesions treated via EEA were described, and the lesions mimicked radiological features of common sellar masses such as craniopharyngiomas and/or pituitary adenomas, and we also report a literature review of similar cases. Methods A retrospective analysis of three primary cases was conducted at the Università degli Studi di Napoli Federico II, Naples, Italy. Clinical information, radiological examinations, and pathology reports were illustrated. Results A total of three cases of so-called “chameleon” sellar lesions comprising two men and one woman were reported. Based on the intraoperative finding and pathological examination, we noticed that case 1 had suprasellar glioblastoma, case 2 had a primary neuroendocrine tumor, and case 3 had cavernous malformation. Conclusion Neurosurgeons should consider “unexpected” lesions of the sellar/suprasellar region in the preoperative differential diagnosis. A multidisciplinary approach with the collaboration of neurosurgeons, neuroradiologists, and pathologists plays a fundamental role. The recognition of unusual sellar lesions can help surgeons with better preoperative planning; so an endoscopic endonasal approach may represent a valid surgical technique to obtain decompression of the optic apparatus and vascular structures and finally a pathological diagnosis.